The Effect of Enriching Tea Infusion with Fruit Additives on Their Antioxidant Properties and the Profile of Bioactive Compounds - Barbara Chilczuk; Małgorzata Materska; Monika Staszowska-Karkut; Marzena Pabich (Applied Sciences)
The aim of the study was to assess the effect of fruit additives on the health-promoting properties of tea infusions. Black and white tea infusions enriched with fruit additives (lemon, quince, strawberry, and sweet pepper) were investigated. To assess the effect of the additives on the properties of the infusions, the content of phenols, antiradical activity, and reducing properties were analysed. The LC-QTOF-MS method facilitated the identification of catechins and the determination of their content. The principal component analysis was used to define the relationship between catechins and the health-promoting properties of the beverages. The research proved that the strawberry and sweet pepper additives improved the quality of the black tea, where the highest antiradical and antioxidant activity was noted. In turn, the additives used for the enrichment of the white tea had a negative effect on its health-promoting properties. The statistical analyses revealed that epicatechin gallate and epicatechin had the greatest impact on the antioxidant properties of the black tea and the white tea, respectively.